2021
DOI: 10.1208/s12248-021-00604-x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of the Prediction of the Unbound Brain-to-Plasma Partitioning Utilizing Machine Learning Approach and Mechanistic Neuropharmacokinetic Model

Abstract: The mechanistic neuropharmacokinetic (neuroPK) model was established to predict unbound brain-to-plasma partitioning (Kp,uu,brain) by considering in vitro efflux activities of multiple drug resistance 1 (MDR1) and breast cancer resistance protein (BCRP). Herein, we directly compare this model to a computational machine learning approach utilizing physicochemical descriptors and efflux ratios of MDR1 and BCRP-expressing cells for predicting Kp,uu,brain in rats. Two different types of machine learning techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Moreover, in silico models for f u,brain were constructed using SVMs by Wan et al [92] and Dolgikh et al [90], both of which demonstrated a relatively high predictive performance with R 2 vales of 0.782 and 0.64, respectively. Interestingly, Kosugi et al [93] demonstrated that ML models combined with both in vitro P-gp and BCRP efflux ratios (ERs) yielded predicted K p,uu,brain values that correlated well with in vivo data when compared to ML models.…”
Section: Unbound Brain-to-plasma Partition Coefficient and Brain Homo...mentioning
confidence: 96%
“…Moreover, in silico models for f u,brain were constructed using SVMs by Wan et al [92] and Dolgikh et al [90], both of which demonstrated a relatively high predictive performance with R 2 vales of 0.782 and 0.64, respectively. Interestingly, Kosugi et al [93] demonstrated that ML models combined with both in vitro P-gp and BCRP efflux ratios (ERs) yielded predicted K p,uu,brain values that correlated well with in vivo data when compared to ML models.…”
Section: Unbound Brain-to-plasma Partition Coefficient and Brain Homo...mentioning
confidence: 96%
“…The BEE score is implemented in MOE software as an SVL utility to predict Kp,uu, and Cu,b (unbound concentration of the molecule in the brain). More recently, Kosugi et al [ 105 ] reported improvement in the predictivity and coverage of application by machine learning approaches for Kp,uu prediction by incorporating in vitro P-gp and BCRP activities.…”
Section: Active Transport Across the Bbb (Efflux Transporters Influx ...mentioning
confidence: 99%
“…Recent mathematical model efforts include incorporation of P-gp efflux ratio 56,57 and BCRP. 58 The Brain Exposure Efficiency Score is another model approach for including influx and efflux active transporters. 59 CNS physiologically-based PK (PBPK) models are more complex by taking into account many PK processes.…”
Section: In Silico Modelsmentioning
confidence: 99%
“…This is because incorporation of active transport at the BBB needs additional attention. Recent mathematical model efforts include incorporation of P‐gp efflux ratio 56,57 and BCRP 58 . The Brain Exposure Efficiency Score is another model approach for including influx and efflux active transporters 59 …”
Section: Assessment Of Bbb Transport and Intra‐brain Distributionmentioning
confidence: 99%